Mapping a hybrid phenomenon in the digital world: The Greek professional gaming scene through Social Network Analysis (SNA) - Dargonaki, Stavroula (The Greek Review of Social Research, 2024)
The consumption of video game content as a commercial spectacle, namely professional gaming, is a complex cultural, social and economic activity that seems to be growing in popularity. The application of Social Network Analysis (SNA) allowed for a graphical representation of the Greek professional gaming scene, specifying its size and the different actors operating within it, and highlighting the crucial role of the content producers themselves. It also revealed the rapid commercialisation of professional gaming and the fact that it is a highly gendered space, where different gendered identities are excluded or marginalised.